Interlayer engineering of a V2O5 anode toward high-rate and durable dual-ion batteries. Issue 1 (18th November 2022) - Qiu, Wenda; Tian, Yunlei; Lin, Shuting; Lei, Aihua; Geng, Zhangqi; Huang, Kaitao; Chen, Jiancong; Huang, Fuchun; Feng, Huajie; Lu, Xihong
Abstract : Dual-ion batteries (DIBs) have gained widespread attention thanks to their high operating voltage, low cost, and environmental friendliness. Abstract : Dual-ion batteries (DIBs) have gained widespread attention thanks to their high operating voltage, low cost, and environmental friendliness. However, the development of DIBs is dramatically limited by the unsatisfactory rate capacity and cycling performance of anode materials. Herein, we adopted a water-incorporation approach to design a V2 O5 anode with an extended interlayer gap (W-V2 O5 ). The incorporated H2 O not only offered ample space and abundant channels for efficient ion/electron intercalation/diffusion, but also improved structural stability during the repeated charge and discharge processes. Consequently, the W-V2 O5 electrode delivered an enhanced specific capacity (293.2 vs. 264.4 mA h g −1 at 1C), rate property (48.2% vs. 24.6% from 1C to 70C), and cycling stability (96.8% vs. 74.6% over 1000 cycles). Furthermore, a DIBs device with fast kinetics was assembled with a graphite cathode and W-V2 O5 NS anode, which could work normally in a wide range of current densities. This work opens a new avenue for designing layered materials for energy-storage devices with high rate and good durability.